2004
DOI: 10.1002/ijc.20416
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic index, glycemic load and risk of prostate cancer

Abstract: Dietary carbohydrates have different glycemic and insulinemic potentials depending on type (glycemic index, GI) and amount (glycemic load, GL) of carbohydrate consumed or both. Insulin in turn has been implicated as a risk factor for several cancers, including that of the prostate. We assessed the relationship of GI and GL with prostate cancer risk in a multicenter case-control study. Dietary factors associated with a Western lifestyle, such as high intakes of refined carbohydrates, fat, meat, dairy foods and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
2
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 44 publications
1
39
2
1
Order By: Relevance
“…Indeed, two recent human studies have suggested that either a highstarch diet [14] or a high glycemic index diet [15] increases prostate cancer risk. These observations seem plausible given that a high carbohydrate diet stimulates insulin production and insulin is a known prostate cancer growth factor [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, two recent human studies have suggested that either a highstarch diet [14] or a high glycemic index diet [15] increases prostate cancer risk. These observations seem plausible given that a high carbohydrate diet stimulates insulin production and insulin is a known prostate cancer growth factor [7].…”
Section: Discussionmentioning
confidence: 99%
“…This raises the interesting possibility that carbohydrate restriction, via lowered insulin levels and perhaps lower IGF-1 levels [13] may delay prostate cancer growth. Indeed, a limited number of human studies suggest that carbohydrate intake may influence prostate cancer biology to a greater extent than fat intake [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of the glycemic index (GI) has provided the scientific community with a new way to examine the quality of carbohydrate (CHO), which has been useful in research on the etiology and prevention of diabetes, coronary heart disease, obesity, prostate cancer, and other chronic diseases [1][2][3][4][5][6]. Historically, CHOs have been classified into two major forms: complex and simple.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that post-prandial elevations in blood glucose concentrations are a signifi cant risk factor for the development of diabetes, cardiovascular disease and certain cancers [1][2][3][4][5] . In contrast, diets based on foods which produce lower post-prandial blood glucose responses (i.e.…”
Section: Introductionmentioning
confidence: 99%